The Effect of Shot Peening Hardening Treatment on Pressure Variation on Mechanical Properties and Microstructure of S45C Steel - Sakuri Sakuri; M. Agung; Nugrah Rekto Prabowo; Utis Sutisna; Reza Azizul Nasa Al Hakim (Jurnal Rekayasa Mesin, 2023)
The purpose of the study was to determine the mechanical properties and microstructure of S45C steel with automatic shot peening treatment. S45C steel is classified as medium steel with a carbon content of 0.51%. Variations of shot peening treatment with varying pressures of 5 bar, 6 bar, and 7 bar. Steel ball shooting uses a size of 0.8 mm, a distance of 100 mm, and a shooting angle of 90o. Hardness test using Vickers and microstructure observation using a microscope. The results of the average hardness test at a pressure of 5 bar are 193.3 VHN, at a pressure of 6 bar with a hardness of 227.2 VHN, and 7 bar with a hardness of 250 VHN. So it can be concluded that the higher the pressure used, the higher the level of hardness obtained. The results of the microstructute photo shown that the higher the pressure released, the more a structure with more martensite phases will be obtained, this has a direct relationship with the hardness of S45C steel.